Exploring Charity Sport Events in Barcelona Province: A Phenomenon on the Rise, albeit with Pending Issues (Explorando los eventos deportivos solidarios en la provincia de Barcelona: un fenómeno en auge con asignaturas pendientes) - Abadia Naudi, Sixte; Cabedo Sanromà, Josep; Sánchez Martin, Ricardo; Medina Luque, F. Xavier; Moragas Rovira, Marta; Morejon Torné, Sacra (Retos, 2019)
Abstract. The purpose of this research was to analyse the main characteristics of charity runs and walks in Barcelona Province, attending at the format of the event, at the organising agents and, with a particular emphasis, at the level of accountability in the management of charitable giving at such events. Data were collected from an analysis of 189 websites for charity runs and walks. A participatory action research group contributed to the development of the analysis model, whose design guided the different stages of the research. The results show the growing popularity of events like these within the context of an ever-increasing diversity of event types and organising agents, as well as the importance placed on charitable causes. A considerable variability is observed in the criteria used for charity management, together with a very low awareness of the need to render account to stakeholders through the website of the events analysed.Resumen. El propósito de esta investigación fue analizar las principales características de las carreras y marchas solidarias en la provincia de Barcelona, en cuanto al formato de los eventos, a los agentes organizadores y, haciendo especial énfasis en el grado de rendición de cuentas en la gestión de la solidaridad de estos eventos. Los datos fueron obtenidos a través del análisis de 189 páginas web de carreras y marchas solidarias. Par ello se diseñó un modelo de análisis desarrollado a partir de las aportaciones de un grupo de investigación social participativa que ha guiado la investigación durante sus diferentes fases. Los resultados muestran la creciente popularidad y auge de este tipo de eventos en un marco de creciente diversidad en cuanto a su tipología, a los propios agentes organizadores y a la importancia otorgada a la causa solidaria. En este sentido, se observa una considerable variabilidad en los criterios utilizados en la gestión de la solidaridad, así como muy poca conciencia de la necesidad de rendir cuentas con los colectivos interesados a través de las páginas web de los eventos analizados.